A complete breeding failure in an Adélie penguin colony correlates with unusual and extreme environmental events - Ropert-Coudert, Yan; Kato, Akiko; Meyer, Xavier; Pellé, Marie; MacIntosh, Andrew J. J.; Angelier, Frédéric; Chastel, Olivier; Widmann, Michel; Arthur, Ben; Raymond, Ben; Raclot, Thierry (Ecography (Copenhagen), 2015)
Among the outcomes of the drastic changes affecting the Earth's ecosystems, nothing is more telling than a complete failure in the reproductive success of a sentinel species: a ‘zero’ year. Here, we found that unusual environmental conditions in the Terre Adélie sector of Antarctica disrupted the breeding activity of Adélie penguins Pygoscelis adeliae on land – but also their foraging activity at sea – to such a degree that no chicks survived in the 2013/2014 breeding season. Uncommonly heavy precipitation for this normally dry desert killed chicks en masse, while weak katabatic winds maintained a persistent sea ice around the colony, thereby impacting chick provisioning by adults. Extreme events such as this have direct repercussions for the species in question, and may also affect the wider sea-ice dependent food web. Understanding the nature, frequency, and consequences of such events are central to the management and conservation of this remote yet crucial ecosystem.